1998
DOI: 10.1002/(sici)1521-4095(199811)10:16<1387::aid-adma1387>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Particles by Templating of Vesicles

Abstract: Template‐directed synthesis is an elegant approach to defined nanostructured materials. Vesicles or liposomes have already been used in the synthesis of small inorganic particles, but their use as a template for polymer synthesis is rare. Despite this, direct templating of vesicles offers interesting new possibilities for the formation of defined nanostructured polymers. While the polymer morphology is determined by the size and shape of the templates, the polymer framework can be modified by conventional chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 12 publications
0
49
0
Order By: Relevance
“…It was shown that encapsulation of QDs into liposomes provides transfer of waterinsoluble QD into aqueous media, facilitates their bioconjugation with proteins, minimizes nonspecific interaction of water-soluble and water-insoluble QD with surface material, and amplifies the analytical signal [2]. A major drawback of liposomes is their instability in vivo and during storage as well as their high sensitivity towards external influences such as variation in temperature, pH and osmotic pressure [26], that can however be overcome through coverage or templating them with different materials, such as a polymer [27] or silica [25]. The most important is that QDs obtained through this approach have substantially increased hydrodynamic diameter which limit their application in bio-imaging and targeting [28].…”
Section: Hydrophilization Of Qdsmentioning
confidence: 99%
“…It was shown that encapsulation of QDs into liposomes provides transfer of waterinsoluble QD into aqueous media, facilitates their bioconjugation with proteins, minimizes nonspecific interaction of water-soluble and water-insoluble QD with surface material, and amplifies the analytical signal [2]. A major drawback of liposomes is their instability in vivo and during storage as well as their high sensitivity towards external influences such as variation in temperature, pH and osmotic pressure [26], that can however be overcome through coverage or templating them with different materials, such as a polymer [27] or silica [25]. The most important is that QDs obtained through this approach have substantially increased hydrodynamic diameter which limit their application in bio-imaging and targeting [28].…”
Section: Hydrophilization Of Qdsmentioning
confidence: 99%
“…It has been shown that the hydrophobic portion of lipid bilayers can be selectively swollen by a variety of hydrophobic monomers, such as styrene [37,38,40,41], alkyl(meth)acrylates [39,42,43] or even lipofullerenes carrying polymerizable octadecadiine side chains [44]. A cross-linking polymerization of such monomers leads to the formation of two-dimensional polymer networks in the interior of the membranes.…”
Section: 3mentioning
confidence: 99%
“…The possible osmosis of QDs through the phospholipid bilayer would results in luminescence decrease, which is undesirable for immunolabel. Leakage of the phospholipid membrane can be halted through the coverage of liposomes with a polymer net [27,28] or silica cover [29,30]. Silica coverage prevents the aggregation of liposomes and the leakage of their content, increasing their stability and facilitating their desiccation and therefore their storage.…”
Section: Introductionmentioning
confidence: 99%